ANALISIS PROSEDUR PENERIMAAN, SELEKSI DAN PENEMPATAN KARYAWAN PADA LPP TVRI SUMSEL BABEL PALEMBANG - M. Ridwan M. Ridwan (Politeknik Negeri Sriwijaya, 2015)
The purpose of this study was to analyze the recruitment procedure, selection and placement of employees in LPP TVRI Sumsel Babel. This study uses qualitative and descriptive analysis techniques. Data in this study was obtained from interviews and questionnaires to 68 employees in LPP TVRI Sumsel Babel. From the results of this research note that the recruitment of employees using a closed system. This is because the financial obstacle of company for open recruitment. From 68 respondents, there are 73.53 percent of respondents aware of any recruitment of families who worked in LPP TVRI Sumsel Babel and the remaining 26.47 per cent know of a friend who works there. to obtain employment in accordance with the job specification, the company should conduct open recruitment.